Climate Risk Country Profile : Lao PDR - World Bank Group; Asian Development Bank (World Bank, Washington, DC and Asian Development Bank, Manila, 2021)
Lao People’s Democratic Republic (PDR) is endowed with abundant natural resources, such as water, forests, minerals, and biodiversity. This document aims to succinctly summarize the climate risks faced by Lao PDR. This includes rapid onset and long-term changes in key climate parameters, as well as impacts of these changes on communities, livelihoods, and economies, many of which are already underway. This is a high-level synthesis of existing research and analyses, focusing on the geographic domain of Lao PDR, therefore potentially excluding some international influences and localized impacts. The core data presented is sourced from the database sitting behind the World Bank Group’s (WBG) climate change knowledge portal (CCKP), incorporating climate projections from the Coupled Model Inter-comparison Project Phase 5 (CMIP5). This document is primarily meant for WBG and Asian Development Bank (ADB) staff to inform their climate actions and to direct them to many useful sources of secondary data and research.